2021
DOI: 10.3390/molecules26113376
|View full text |Cite
|
Sign up to set email alerts
|

Diketopiperazine Gels: New Horizons from the Self-Assembly of Cyclic Dipeptides

Abstract: Cyclodipeptides (CDPs) or 2,5-diketopiperazines (DKPs) can exert a variety of biological activities and display pronounced resistance against enzymatic hydrolysis as well as a propensity towards self-assembly into gels, relative to the linear-dipeptide counterparts. They have attracted great interest in a variety of fields spanning from functional materials to drug discovery. This concise review will analyze the latest advancements in their synthesis, self-assembly into gels, and their more innovative applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 120 publications
0
27
0
Order By: Relevance
“…Considering that the shorter the motif, the lower and easier will be the cost of production, it is thus not surprising that ultra-short peptides are amongst the most attractive supramolecular peptide gelators [46]. In particular, cyclic [47][48][49] or linear dipeptides [50][51][52][53][54][55] are amongst the simplest options as building blocks for hydrogels, however, tripeptides are better positioned for bioactivity. Indeed, it was shown that 25 atoms other than hydrogen constitute the ideal size for drugs and drug-like molecules for maximal ligand-binding efficacy and bioactivity, and this number corresponds to the average number for a tripeptide [56].…”
Section: Self-assembling Short Peptides With Bioactive Motifs For Hyd...mentioning
confidence: 99%
“…Considering that the shorter the motif, the lower and easier will be the cost of production, it is thus not surprising that ultra-short peptides are amongst the most attractive supramolecular peptide gelators [46]. In particular, cyclic [47][48][49] or linear dipeptides [50][51][52][53][54][55] are amongst the simplest options as building blocks for hydrogels, however, tripeptides are better positioned for bioactivity. Indeed, it was shown that 25 atoms other than hydrogen constitute the ideal size for drugs and drug-like molecules for maximal ligand-binding efficacy and bioactivity, and this number corresponds to the average number for a tripeptide [56].…”
Section: Self-assembling Short Peptides With Bioactive Motifs For Hyd...mentioning
confidence: 99%
“…In this context, they have high stability, while the costs of production are low. Moreover, they can be produced and modified in large quantities in an easy way [370]. DKP-based low molecular weight gelators also find applications in encapsulation of drugs [74,370].…”
Section: Supramolecular Structuring Of Dkpsmentioning
confidence: 99%
“…Moreover, they can be produced and modified in large quantities in an easy way [370]. DKP-based low molecular weight gelators also find applications in encapsulation of drugs [74,370]. Self-assembled functional proline containing DKP-based bio-nano-materials have superior structural rigidity and in vivo stability provided by the DKP ring.…”
Section: Supramolecular Structuring Of Dkpsmentioning
confidence: 99%
See 1 more Smart Citation
“…21 The synthetic molecules, metabolites, or natural products with CDP core showed numerous biological activities such as anticancer, antimalarial, antimicrobials, hypoglycaemic agents, quorum sensing, blood-brain barrier (BBB) transporters, drug delivery vehicles, tissue engineering, and so on. [22][23][24][25][26][27][28] CDPs exhibit high structural rigidity, low enzymatic degradation, high physiological stability, and exceptional biological activity as compared to their linear counterparts. 19,29 Limited conformational mobility and presence of four hydrogen-bonding sites (two donors and two acceptors) of two cis amide groups in CDPs 30,31 strongly encourage the self-assembly and formation of gels.…”
Section: Introductionmentioning
confidence: 99%